Isolation and identification of rhizospheric bacteria associated with lemongrass for bioremediation of dibenzofuran contaminated soil - Sanusi, Najwa Husna; Phang, Ing Chia; Nordin, Noor Faizul Hadry (2015)
Contamination of soil and groundwater pollution is a severe problem, has been attracting considerable public attention over the last decades. The negative effects of pollutants on the environment and on the human health are diverse depend on the nature of the pollution. Thus, bioremediation offer a sustainable solution to the problem of contaminated environmental soil. With the demand for green and cleaner technology for remediation process, there is an increased interest in moving away from conventional technologies towards bioremediation technologies. Rhizospheric zone is a suitable place for harboring bacteria that are capable to utilize these chemical compounds which will be used either to facilitate growth of bacteria or the host plants. Identification of the specific microbial members should allow for better strategies to enhance biodegradation. This study aimed to isolate and identify the rhizospheric associated microbes of lemongrass (Cymbopogon citratus), a plant that commonly available in South East Asia. This probably is due to their ability to harbor large number of bacteria on their highly branched root systems. Total of 68 bacteria were isolated from the rhizospheric soil of lemongrass from 2 different unpolluted sites. Genomic DNA of the bacteria was successfully isolated and Polymerase Chain Reaction (PCR) amplification of 16S rRNA gene was achieved using 27F and 1492R primers. Purified PCR products from chosen samples were sent for sequencing. The identification of the bacteria was confirmed by sequence homology 16S rRNA gene studies. Several identified microbial strains isolated from rhizospheric zone, both Gram-negative (mainly the genera Enterobacter sp., Klebsiella sp., Aeromonas hydrophila, Chromobacterium sp., Pseudomonas fulva, Burkholderia sp., Citrobacter werkmanii, Stenotrophomas maltophilla, and Pantoea agglomerans) and Gram-positive bacteria (predominantly belonging to the genera Staphylococcus succinus and Staphylococcus saprophyticus). In degradation studies, the isolates showed the ability to utilize dibenzofuran up to 100 ppm with higher growth rate in utilizing the dibenzofuran. According to the result obtained, indigenous bacteria from rhizospheric soil of lemongrass were found to be able to degrade dibenzofuran hence can be utilized in bioremediation.